Paradise Reconsidered in Gnostic Mythmaking. Rethinking Sethianism in the Light of the Ophitic Evidence. By Tuomas Rasimus - Edwards, Mark (The journal of theological studies, 2011)
In the ancient heresiologists Ophites, Naassenes, Barbeloites, and Sethians have been woven into a Gordian knot so dense that it would bury any sword that tried to cleave it. They can all be differentiated from the Valentinians by negatives: the lack of a named heresiarch, the amorphous character of their extant writings, the opacity and infrequency of tenets or terms that are manifestly scriptural. Some deny that any patristic categories can help us through this imbroglio; others contend that the Sethians admit of demarcation, the rest being merely branches, scions, or chimerical representations of this group.